2001
DOI: 10.1074/jbc.m009187200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Type 1α cGMP-dependent Protein Kinase Using Green Fluorescent Fusion Proteins

Abstract: The cGMP-dependent protein kinases (PKGs) are ubiquitous effector enzymes that regulate a variety of physiological processes in response to nitric oxide and natriuretic agonists. We have constructed green fluorescent fusion proteins (GFP) using full-length (PKG-GFP) and truncations encoding either the regulatory domain of PKG1␣ (G1␣R-GFP) or the catalytic domains of PKG1␣ (GFP-G1C) to examine the enzymatic properties and intracellular location. When transiently transfected into mammalian cells, these construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
(40 reference statements)
0
42
1
Order By: Relevance
“…95,99 -102 However, other investigators found no evidence of PKG nuclear translocation in primary VSMCs, HEK293, and CV-1 cells, or observed nuclear PKG only in a minority of the cell population. 97,103,104 Based on recent findings, we have speculated that PKG may be retained in extranuclear compartments by binding to cell…”
Section: Creb and Atf-1mentioning
confidence: 99%
“…95,99 -102 However, other investigators found no evidence of PKG nuclear translocation in primary VSMCs, HEK293, and CV-1 cells, or observed nuclear PKG only in a minority of the cell population. 97,103,104 Based on recent findings, we have speculated that PKG may be retained in extranuclear compartments by binding to cell…”
Section: Creb and Atf-1mentioning
confidence: 99%
“…28,29 Additionally, the role of the 3Ј-UTR region was proven by using ECE-1 transgenes with (pCMV6-UTR-ECE1) or without this region (pCMV6-ECE1) (Please see Supplemental data). PKG involvement was studied using a dominant-negative form and a constitutively active construct of PKG-1␣, 30,31 which were kindly donated by Dr D. Browning (Medical College of Georgia, Augusta, GA).…”
Section: Transient Transfection Experimentsmentioning
confidence: 99%
“…7A, bottom). Although a nonspecific interaction between PKG and Raf-1 cannot be definitively excluded, the capacity of the catalytic region of PKG1␣ to interact with the full-length and the regulatory regions has been previously shown (Browning et al, 2001). In addition, the complex is inducible and time-sensitive, supporting the idea that Raf-1 is a target of PKG in the aortic endothelium (Fig.…”
mentioning
confidence: 99%